Adaptasi dan Transformasi Ekonomi Digital di Pasar Tradisional Aur Kuning Bukittinggi dalam Kajian Sejarah Sosial-Ekonomi (2009-2023) - Arini, Dini Farhati; Zulqaiyyim, Zulqaiyyim; Djalius, Yusmarni (MUKADIMAH: Jurnal Pendidikan, Sejarah, dan Ilmu-ilmu Sosial, 2025)
The rapid development of information technology has significantly influenced societal lifestyles, including in the economic sector. This study examines the adaptation and transformation of traditional markets in response to digitalization, with a particular focus on Aur Kuning Market in Bukittinggi, a major economic hub in the region. The research employs a historical method, utilizing both primary and secondary sources, including oral and written data. The findings reveal that traders in Aur Kuning Market are gradually adopting digital tools, albeit primarily for communication rather than full-fledged e-commerce. Despite the growing digital presence, traders strive to maintain the traditional characteristics of the market. The study highlights the coexistence of conventional market practices with modern digital tools and underscores the challenges and opportunities associated with this transition.